Two new species of the stenopodidean shrimp genus Spongiocaris Bruce & Baba, 1973 (Crustacea: Decapoda: Spongicolidae) from the Indo-West Pacific - Komai, Tomoyuki; Grave, Sammy De; Saito, Tomomi (Zootaxa, 2016)
Two new species of the deep-water spongicolid genus Spongiocaris Bruce & Baba, 1973, are described and illustrated from two localities in the Indo-West Pacific. Spongiocaris panglao n. sp. is described on the basis of material from the Bohol Sea, the Philippines, at depths of 220–731 m. Spongiocaris tuerkayi n. sp. is described on the basis of material from Atlantis Bank in the southwestern Indian Ocean at depths of 743–1053 m. Among eight known congeners, both new species appear close to S. semiteres Bruce & Baba, 1973, differing in the rostral length and armature, shape of the carapace, telsonal armature, development of the grooming apparatus of the first pereopod and shape of the third pereopod chela. An identification key to the species currently assigned to Spongiocaris is presented.